Perancangan Warehouse Management System Berbasis IOT Pada PT. Agility Internasional - Bayu Saputra; Richardus Eko Indrajit; Erick Dazki (Universitas PGRI Kanjuruhan Malang, 2021)
The process management of goods contained in PT Agility International's warehouse do manually, where each employee will enter item SKU data into the enterprise resource planning system. The recording process takes a long time and requires many workers who have to do the work. Recording the goods will include the processing entering the warehouse (inbound), monitoring the number is good in the warehouse system, and the process of goods leaving the warehouse for the delivery process. By utilizing the RFID tag in each item used as the serial number of the item, this study will apply the Internet of Things technology to automate the management system in the PT warehouse. Agility International. The process of reading data from each RFID tag that is in each item will later utilize an RFID UHF Reader device with a data reading radius of around 10 meters. With this, the process of recording incoming goods (inbound), asset monitoring, and recording goods that will come out of the warehouse can do automatically. It is undoubtedly very beneficial for the sustainability of existing business processes in a warehouse.